Acacias in 'remedial' agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The urgent need for large-scale reforestation programmes to reverse the environmental degradation in tropical areas is becoming increasingly obvious. However, the lack of a selection of fast-growing, multi-purpose trees for differing eco-systems,...